Molecular footprints of selection effects and whole genome duplication (WGD) events in three blueberry species: detected by transcriptome dataset - Wang, Yunsheng (BMC Plant Biol, 2020)
BACKGROUND: Both selection effects and whole genome duplication played very important roles in plant speciation and evolution, and to decipher the corresponding molecular footprint has always been a central task of geneticists. Vaccinium is species rich genus that comprised of about 450 species, and blueberry is one of the most important species of Vaccinium genus, which is gaining popularity because of high healthful value. In this article, we aimed to decipher the molecular footprints of natural selection on the single copy genes and WGD events occur in the evolutionary history of blueberry species. RESULTS: We identified 30,143, 29,922 and 28,891 putative protein coding sequences from 45,535, 42,914 and 43,630 unigenes assembled from the leaves’ transcriptome assembly of 19 rabbiteye (T1), 13 southern highbush (T2) and 22 northern highbush (T3) blueberry cultivars. A total of 17, 21 and 27 single copy orthologs were found to undergone positive selection in T1 versus T2, T1 versus T3, and T2 versus T3, respectively, and these orthologs were enriched in metabolic pathways including “Terpenoid backbone biosynthesis”, “Valine, leucine and isoleucine biosynthesis”, “Butanoate metabolism”, “C5-Branched dibasic acid metabolism” “Pantothenate and CoA biosynthesis”. We also detected significant molecular footprints of a recent (about 9.04 MYA), medium (about 43.44 MYA) and an ancient (about 116.39 MYA) WGD events that occurred in the evolutionary history of three blueberry species. CONCLUSION: Some important functional genes revealed positive selection effect in blueberry. At least three rounds of WGD events were detected in the evolutionary history of blueberry species. Our work provides insights about the genetic mechanism of adaptive evolution in blueberry and species radiation of Vaccinium in short geological scale time.